2021
DOI: 10.3390/diagnostics11050750
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Interventional Radiology Management of Ureteral Iatrogenic Leakage after Gynecologic Surgery

Abstract: Objective: To report safety and efficacy of interventional radiology procedures in the treatment of gynecologic iatrogenic urinary leaks. Methods: A retrospective analysis of iatrogenic ureteral lesions treated between November 2009 to April 2019 was performed. Under ultrasound (US) and fluoroscopy guidance, an attempt to place a ureteral stent and nephrostomy was carried out in the same session using an anterograde percutaneous approach. At the end of any procedure, a fluoroscopic control and a cone-beam CT s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Ku et al 3 reported a complete resolution rate of 65% in 17 patients with urinary leak treated with both antegrade and retrograde ureteral stent placement. Fontana et al 16 performed ureteral stent placement in 15 patients with urinary leak and reported a complete resolution rate of 53.5%. However, Ustunsoz et al 17 reported a complete resolution rate of 75% in 22 patients with 24 ureteral injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Ku et al 3 reported a complete resolution rate of 65% in 17 patients with urinary leak treated with both antegrade and retrograde ureteral stent placement. Fontana et al 16 performed ureteral stent placement in 15 patients with urinary leak and reported a complete resolution rate of 53.5%. However, Ustunsoz et al 17 reported a complete resolution rate of 75% in 22 patients with 24 ureteral injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of ureteral injuries (UI) increases significantly during procedures for malignant neoplasms of the genitals [1,2]. Incidences of bilateral UIs are rare, and being reported as isolated cases, but their occurrence present considerable treatment challenges [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, in the event of such an occurrence, the risk of damaging the ureter is increased, where urinary leakage is seen from the wounded ureter [ 45 , 46 , 47 ]. Therefore, a ureteroraphy or segmental ureterectomy with anastomosis should be performed [ 48 , 49 ]. Similarly, in such cases where the ureter was identified before damaging it, there can still be no option to avoid the ureterectomy due to the impossibility of manipulating it out of the herniation process.…”
Section: Introductionmentioning
confidence: 99%